Projeções de vazões afluentes à usina elevatória Santa Cecília (RJ) a partir de cenários de desmatamento da floresta amazônica e de mudanças climáticas - Cabral, Rafael Livolis de Alcantara (2017)
This study seeks to identify the possible impacts on the natural inflow in the Guandu river system using hydrologic modeling based on the response of two different components of the climate system to human action. We used three hypothetical scenarios of deforestation in the Amazon (15%, 50% and 100%) and four future greenhouse gases (GHG) emissions scenarios. The monthly version of hydrologic model SMAP was used. The model was calibrated with precipitation data from National Water Agency (ANA) and natural flow data from Electric System National Operator (ONS). In the forecast phase, climate forecast data from CAM3.1 model (based on deforestation scenarios) and from GFDL-CM2.1 model with support of emissions scenarios were used. As conclusion of this study, it was found that the changes from deforestation are less linear and more complex than those coming from emission scenarios, where the relationship between climate change impacts and anthropogenic action have been clearer. Based on emission scenarios, we highlight the possibility of a reduction of 20% to 80% on the average inflow rate to Santa Cecília by the end of this century.